2021
DOI: 10.1101/2021.07.28.453943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural insights into tick-borne encephalitis virus neutralization and animal protection by a therapeutic antibody

Abstract: Tick-borne encephalitis virus (TBEV) causes about 5-6 thousand cases annually, while there is still no effective treatment for this virus. To fill this gap, a high-affinity chimeric anti-TBEV antibody ch14D5 has previously been constructed, and high protective activity in a murine TBEV model has been shown for this antibody. However, the mechanism of action of this antibody and the recognized epitope have not been known yet. In this study, it is shown by X-ray crystallography that this antibody recognizes a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The superposition of the iTBEV E protein domain III with the corresponding regions of 5O6V, 6J5F, and 7LSE by C α atoms showed that our iTBEV has the same conformation of the main chain for the epitopes of all three antibodies ( Figure 4 ). An X-ray structure of a therapeutic antibody ch14D5 with TBEV E protein DIII was also reported, but not yet published [ 34 ]. The superposition of the epitope of this antibody (residues 308–315, 331–336, 367, and 387) on the DIII structure of TBEV-Sofjin (PDB ID 7LSE) with the corresponding regions of our structure also did not reveal substantial differences (Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…The superposition of the iTBEV E protein domain III with the corresponding regions of 5O6V, 6J5F, and 7LSE by C α atoms showed that our iTBEV has the same conformation of the main chain for the epitopes of all three antibodies ( Figure 4 ). An X-ray structure of a therapeutic antibody ch14D5 with TBEV E protein DIII was also reported, but not yet published [ 34 ]. The superposition of the epitope of this antibody (residues 308–315, 331–336, 367, and 387) on the DIII structure of TBEV-Sofjin (PDB ID 7LSE) with the corresponding regions of our structure also did not reveal substantial differences (Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Potent orthoflaviviral neutralizing antibodies have been shown to interfere with the process of virus-induced membrane fusion ( 83 , 109 , 110 ). Other antibodies are thought to block the binding of the virion to cellular receptors, block the interaction of the virion with cellular receptors through steric hindrance, or block membrane fusion inside endosomes or phagosomes through the cross-linking of E molecules ( 111 ). It is plausible that the mechanism of neutralization of many E-specific antibodies involves both steps of virus entry and is modulated by the composition of antibody populations in polyclonal sera ( 108 ), complicating potential therapeutic development.…”
Section: Humoral Immune Responses In Tbev Infection and Vaccinationmentioning
confidence: 99%